2020
DOI: 10.1186/s40834-020-00105-w
|View full text |Cite
|
Sign up to set email alerts
|

Contraception need and available services among incarcerated women in the United States: a systematic review

Abstract: Context: Seventy-five percent of incarcerated women are of reproductive age, most of whom are at-risk for unintended pregnancy. Women who are incarcerated come disproportionately from socioeconomically disadvantaged backgrounds and often lack access to desired reproductive health care. While the carceral system provides a unique opportunity to fill this gap, a better understanding of the contraceptive needs, desires, and plans of incarcerated women is needed to optimize health care provision within the carcera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…The results of this study are consistent with prior research. US studies involving women in prison [1][2][3]12,13,[25][26][27] have also identified barriers to accessing contraception in prison and after release, despite women's interest in and motivation to access contraception [1,13,28]. A small number of studies have used qualitative approaches to explore reproductive health issues among women in prison [10,16,17,29]; these studies examined specific issues such as sterilization [16] and the prevention of sexually transmitted infections on release [29].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of this study are consistent with prior research. US studies involving women in prison [1][2][3]12,13,[25][26][27] have also identified barriers to accessing contraception in prison and after release, despite women's interest in and motivation to access contraception [1,13,28]. A small number of studies have used qualitative approaches to explore reproductive health issues among women in prison [10,16,17,29]; these studies examined specific issues such as sterilization [16] and the prevention of sexually transmitted infections on release [29].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that women in prison are made to feel like their health concerns are not legitimate has been echoed in other work [ 31 , 32 ]. Previous studies have identified that some women see their time in prison as an opportunity to access healthcare [ 31 , 33 ], including contraceptive services [ 13 ]. A recent Canadian study conducted focus groups with 11 admitted women and six healthcare staff in a provincial correctional facility, and similar to our study, found that factors influencing the use of women’s health services in prison were lack of gender-specific services, mistrust of healthcare providers, and fragmentation of healthcare [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations